Effects of different exercise interventions on lower back pain: a systematic review and meta-analysis - Liu, X.; Gao, W.; Wu, P.; Huang, J.; Han, J.; Xu, X.; Chen, W. (Frontiers in Physiology, 2025)
Objective: Lower back pain (LBP) is the leading cause of disability worldwide. This study evaluates the pain relief and functional benefits of exercise interventions for affected individuals to inform clinical practice.